Assembly of organic–inorganic hybrid materials constructed from polyoxometalate and metal–1, 2, 4-triazole units: synthesis, structures, magnetic, electrochemical and photocatalytic properties1. Issue 10 (14th March 2015) - Jiao, Yan-Qing; Qin, Chao; Zang, Hong-Ying; Chen, Wei-Chao; Wang, Chun-Gang; Zheng, Tian-Tian; Shao, Kui-Zhan; Su, Zhong-Min
<x xml:space="preserve">Abstract</x> A family of organic–inorganic hybrids built by Keggin/Dawson POMs with metal–1, 2, 4-triazole units has been synthesized through modulating the pH value.